PERANCANGAN SISTEM INFORMASI INDEKS ALAMAT PASIEN MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI PUSKESMAS CIBEUNYING - Fivra Margeritta Maro; Meira Hidayati; Riky Faza (POLITEKNIK PIKSI GANESHA, 2021)
Address Index is a tabulation of data containing the addresses/regions of patients who have been treated at the Puskesmas. The Cibeunying Health Center in indexing patient addresses has been computerized, namely by connecting to SIMPUS and quite effective in recapitulation, it has been computerized by recapitulating patient data whose addresses are not clear or not indexed. Then it is computerized. accurate. Information technology, which is a combination of computer technology and telecommunications, changes the industrial paradigm to a post-industrial paradigm which means it also changes the behavior of the business or business environment, which means that information technology gains closeness between business people and their customers, because this shortens the distance and time. Design model using SDLC Planning (Planning), Analysis (Analysis), Design (Design), Implementation (Implementation), Maintenance (Maintenance). Address Index Information System Address at Puskesmas Cibeunying, to input a computerized address index report that is directly connected by the health office can be called SIMPUS. The medical record installation officer no longer needs to type in Microsoft excel and then move it again, if there is an error in the address, just go to the registration section directly to see more details. If it is complete, all patient address indexes will be effective and efficient. Keywords: Index of addresses, information, health centers.